2012
DOI: 10.1016/j.biomaterials.2012.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 multivalent HPMA copolymer-Fab′ conjugates for the direct induction of apoptosis

Abstract: A hybrid biomimetic system comprising high-molecular-weight, linear copolymer of N-(2-hydroxypropyl)methacrylamide (HPMA) grafted with multiple Fab′ fragments of anti-CD20 monoclonal antibody (mAb) was synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization followed by attachment of Fab′ fragments via thioether bonds. Exposure of human non-Hodgkin’s lymphoma (NHL) Raji B cells to the multivalent conjugates resulted in crosslinking of CD20 receptors and commencement of apoptosis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…A copolymer of HPMA and APMA was synthesized using reversible addition-fragmentation chain transfer (RAFT) polymerization as previously described [28]. Briefly, the monomers HPMA and APMA, chain transfer agent CPDB, and V-501 were placed in an ampule and sealed after bubbling the solution with nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…A copolymer of HPMA and APMA was synthesized using reversible addition-fragmentation chain transfer (RAFT) polymerization as previously described [28]. Briefly, the monomers HPMA and APMA, chain transfer agent CPDB, and V-501 were placed in an ampule and sealed after bubbling the solution with nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we attempted to increase the valence by using branched polymer backbones 113,114 or linear, high-MW copolymers synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization. 115 Other researchers used biological polymers such as DNA or polypeptides as scaffolds to attach antibodies or the smaller size single-chain variable fragments (scFv). 17,116 These polyvalent constructs indeed achieved better efficacies than their monovalent counterparts.…”
Section: Design Of Drug-free Macromolecular Therapeuticsmentioning
confidence: 99%
“…Previously we have shown that, in addition to the valence, the MW of the polymer backbone also had a positive influence on the efficiency of CD20 crosslinking and apoptosis in vitro . 115 In the body, HPMA copolymers with larger MW tend to circulate longer in the blood. 64,65 This characteristic is favorable for targeting blood cancers such as lymphomas.…”
Section: Advantages Of Drug-free Macromolecular Therapeuticsmentioning
confidence: 99%
“…The hydrodynamic diameter of Mal-DACHPt/m remained close to 30 nm even after Fab' conjugation (Tables 1 and 2). This might be reasonable considering the diameter of Fab' as that of a volumeequivalent sphere of 4e6 nm [46] (Table 2). This relatively small size of anti-TF Fab'-DACHPt/m could be a significant advantage for effective extravasation and penetration in stroma-rich tumor tissues of pancreatic cancer [35].…”
Section: Conjugation Of Antibody Fragments To Maleimidefunctionalizedmentioning
confidence: 98%